The Kindship Terms In Gayonese Ethnic Group Gayo Takengon, Central Aceh – Indonesia - Ali Amran (English Teaching and Linguistics Journal (ETLiJ), 2021)
This study aims to investigate, analyze and discuss the kinship terms of Gayonese ethnic group in Gayo land, Takengon Central Aceh - Indonesia. This descriptive qualitative study also aims to translate those Gayonese kinship terminologies into English. In this study the terms ‘ama’ and ‘ine’ have culturally different functions and meanings. To find the sample, the researcher applied some positive random sampling techniques. It means that, in deciding the samples that were used, some criteria were also applied. Kinship terms, the address used to indicate kinship, such as great-grand-parents, grandparents, father and mother, husband and wife, brother and sister, uncle and aunty, elder brother and elder sister, younger brother and younger sister etc. First, the function of kinship terms are closely related to their relatives (based on blood relationship). Second, the function of the familiar terms of the greeting terms (based on blood relationship). Finally, the functions of kinship terms are addressed terms. As a result, politeness is almost impossible without understanding and applying the cultural concept.